IMAGE OF REALISM AT THE ARABIC POEMS OF SAADI SHERAZI: ANALYTICAL STUDY - Majid Merhej (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The scientific approach requires to search realism at Saadi Shirazi Arabic poems. The researcher has to seek and collect data and information from different trends. Also, taking different paths or scientific assumptions that include variables to reach the causes, and in the light of that the image will be perfectly clear to study the realistic image of the poet Saadi Shirazi analytically based on the clear evidences, proves and criteria. In this paper, the phases of realistic image will be studied individually at Saadi Shirazi's poets (Analytical study). He is recognized for the quality of his writings and for the depth of his social and moral thoughts. Realism is the conclusion of Philosophical thought, which means the real knowledge or the real realistic of things without fake or external nature reflection toward the individual behavior, which is a clear concept of realism. Realism is the truth in saying things. The truth is that realism one of the old concepts that showed up in the 18 century, but its image manifested since the ancient times, and that what we found in many poets works at Abassid era such as: Al-Mutnabi, Saadi Shirazi and Abu Al-Alaa Al-Meari. In this paper, the realism of poetic works to the Iranian inspired poet Saadi Shirazi will be studied . He is one of literature Persian poets and one of the thought liberators at Persia , and his main subjects are Eulogy, flirting and sermon. He praised Baghdad through his poetic lines that characterized with proud, excitement ,praise and satire. He presented to some mental issues realistically such as wisdom, philosophy, idioms, asceticism, mysticism and others. The poet mental trends was influenced by the Abbasid civilization because this kind of environment include all the Natural, political, scientific, social, Art and literal effects even the emotional one, and that can be seen in his poetic work away from fake. He named as a similar to Al-Mutanabi in Persian literature . He was effected by many Arab poets such as Abu Al-Taiyb Al-Mutanabi, and most of his works are in Arabic language. The best he wrote in is Baghdad after being destroyed by Tatars. It is considered one of the realistic poems, his words express how greatly he loves Baghdad and the reality of Destruction. The search will continue about realism, praising, flirting, wisdom and others in his Arabic poetic works. Truth is one of the realistic images, thought can be expressed clearly with no doubt. Truth and Realism are a chronic thoughts. The research analytical approach is to implement the image of realistic, so the paper has divided to many sections. The main of his work is " Klistan Saadi" and "The Orchard". As a result of his influence of Arabic language he wrote many poems in Arabic language. So, many critics in Arabic and Persian literature considered him as one of the influenced poets of Arabic language.